Characterization of Enzymatically Synthesized Titania Thin Films Using Positron Annihilation Spectroscopy Reveals Low‐Cost Approach for Organic/Inorganic Photovoltaic Cells. (3rd March 2020) - van Amelrooij, Edward F.; Schut, Henk; Egger, Werner; Dickmann, Marcel; Hugenschmidt, Christoph; Mallée, Lloyd; Hanefeld, Ulf; McMillan, Duncan G. G.; Eijt, Stephan W. H.
Abstract: A new method is developed to produce mesoporous titania thin films at room temperature using the enzyme papain in a dip‐coating procedure, providing low‐cost titania films in a sustainable manner. Quartz crystal microbalance, positron annihilation Doppler broadening and lifetime spectroscopy, scanning electron microscopy, and X‐ray diffraction are used to determine the deposition and structural properties of the films. As‐deposited films have low densities ρ ≈ 0.6 g cm −3, contain small micropores and proteins, and exhibit corrugated surfaces. Annealing at temperatures of 300 °C or higher leads to the destruction and evaporation of most of the organic material, resulting in a thickness decrease of 50–60%, more pure titania films with increased density, an increase in micropore size and a decrease in the concentration and size of atomic‐scale vacancies. Up to 50 layers could be stacked, allowing easy control over the total layer thickness. Based on these titania films, first test devices consisting of natural dye‐sensitized solar cells are produced, that show photovoltaic activity and indicate possibilities for low‐cost, accessible, organic production of solar cells. Given the wide range of other applications for titania, this new method is a promising candidate for improving the fabrication of those products with respect to cost, sustainability, and production speed. Abstract : Papain/titania single and multilayer thin films are synthesized at room temperature using biomineralization by a flexible dip‐coating procedure using papain and titanium(IV) bis(ammonium lactato)dihydroxide (TiBALDH) aqueous solutions. The organic component is effectively removed by moderate thermal annealing, resulting in nanoporous titania films with a high surface area and low vacancy concentrations, showing promise for low cost applications in photovoltaic devices.